Dopaminergic, serotonergic, and noradrenergic deficits in Parkinson disease - Buddhala, Chandana (Ann Clin Transl Neurol, 2015)
OBJECTIVE: People with Parkinson disease (PD) frequently develop dementia, which is associated with neocortical deposition of alpha-synuclein (α-syn) in Lewy bodies and Lewy neurites. In addition, neuronal loss and deposition of aggregated α-syn also occur in multiple subcortical nuclei that project to neocortical, limbic, and basal ganglia regions. Therefore, we quantified regional deficits in innervation from these PD-affected subcortical nuclei, by measuring the neurotransmitters and neurotransmitter transporter proteins originating from projections of dopaminergic neurons in substantia nigra pars compacta, serotonergic neurons in dorsal raphé nuclei, noradrenergic neurons in locus coeruleus, and cholinergic neurons in nucleus basalis of Meynert. METHODS: High-performance liquid chromatography and novel enzyme-linked immunosorbent assays were performed to quantify dopaminergic, serotonergic, noradrenergic, and cholinergic innervation in postmortem brain tissue. Eight brain regions from 15 PD participants (with dementia and Braak stage 6 α-syn deposition) and six age-matched controls were tested. RESULTS: PD participants compared to controls had widespread reductions of dopamine transporter in caudate, amygdala, hippocampus, inferior parietal lobule (IPL), precuneus, and visual association cortex (VAC) that exceeded loss of dopamine, which was only significantly reduced in caudate and amygdala. In contrast, PD participants had comparable deficits of both serotonin and serotonin transporter in caudate, middle frontal gyrus, IPL, and VAC. PD participants also had significantly reduced norepinephrine levels for all eight brain regions tested. Vesicular acetylcholine transporter levels were only quantifiable in caudate and hippocampus and did not differ between PD and control groups. INTERPRETATION: These results demonstrate widespread deficits in dopaminergic, serotonergic, and noradrenergic innervation of neocortical, limbic, and basal ganglia regions in advanced PD with dementia.